Physico-mechanical properties of chitosan films with carvacrol and grape seed extract - Rubilar, J. F. (2013)
The physico-mechanical properties of 3 films composed by carvacrol, grape seed extract (GSE) and chitosan in different proportions were studied. The films, prepared by solvent casting technique with the following compositions of the casting solutions in carvacrol, GSE and chitosan: film-1: 9.6 ppm–684 ppm–1.25% w/v, film-2: 60 ppm–400 ppm–1.2% w/v and film-3: 90 ppm–160 ppm–1.24% w/v and were compared to a control (1.25% w/v chitosan) film. Mechanical, structural, barrier and colour properties of the films were evaluated. Film-3 presented the lowest water vapour and carbon dioxide permeabilities (WVP and CO2P) and tensile strength (TS) values and the highest oxygen permeability (O2P), whereas film-1 presented the highest water content and the lowest crystallinity, CO2P, TS and luminosity. These results suggest that in the range studied, carvacrol and GSE affect the film structure and its mechanicalproperties due to hydrophilic (GSE) and hydrophobic (carvacrol) compounds. This work will help the development of edible films, based on physico-mechanicalproperties, contributing to food preservation and shelf-life extension.